Introducing malaria rapid diagnostic tests in private medicine retail outlets: A systematic literature review. - Theodoor Visser; Katia Bruxvoort; Kathleen Maloney; Toby Leslie; Lawrence M Barat; Richard Allan; Evelyn K Ansah; Jennifer Anyanti; Ian Boulton; Siân E Clarke; Jessica L Cohen; Justin M Cohen; et al. (PLoS ONE, 2017)
Background Many patients with malaria-like symptoms seek treatment in private medicine retail outlets (PMR) that distribute malaria medicines but do not traditionally provide diagnostic services, potentially leading to overtreatment with antimalarial drugs. To achieve universal access to prompt parasite-based diagnosis, many malaria-endemic countries are considering scaling up malaria rapid diagnostic tests (RDTs) in these outlets, an intervention that may require legislative changes and major investments in supporting programs and infrastructures. This review identifies studies that introduced malaria RDTs in PMRs and examines study outcomes and success factors to inform scale up decisions. Methods Published and unpublished studies that introduced malaria RDTs in PMRs were systematically identified and reviewed. Literature published before November 2016 was searched in six electronic databases, and unpublished studies were identified through personal contacts and stakeholder meetings. Outcomes were extracted from publications or provided by principal investigators. Results Six published and six unpublished studies were found. Most studies took place in sub-Saharan Africa and were small-scale pilots of RDT introduction in drug shops or pharmacies. None of the studies assessed large-scale implementation in PMRs. RDT uptake varied widely from 8%-100%. Provision of artemisinin-based combination therapy (ACT) for patients testing positive ranged from 30%-99%, and was more than 85% in five studies. Of those testing negative, provision of antimalarials varied from 2%-83% and was less than 20% in eight studies. Longer provider training, lower RDT retail prices and frequent supervision appeared to have a positive effect on RDT uptake and provider adherence to test results. Performance of RDTs by PMR vendors was generally good, but disposal of medical waste and referral of patients to public facilities were common challenges. Conclusions Expanding services of PMRs to include malaria diagnostic services may hold great promise to improve malaria case management and curb overtreatment with antimalarials. However, doing so will require careful planning, investment and additional research to develop and sustain effective training, supervision, waste-management, referral and surveillance programs beyond the public sector.